Edge odd graceful labeling of some path and cycle related graphs. Issue 2 (1st August 2017) - Daoud, S.N.
Abstract: Solairaju and Chithra introduced a new type of labeling of a graph G with p vertices and q edges called an edge odd graceful labeling if there is a bijection f from the edges of the graph to the set { 1, 3, …, 2 q − 1 } such that, when each vertex is assigned the sum of all edges incident to it m o d 2 k, where k = max ( p, q ), the resulting vertex labels are distinct. In this paper we proved necessary and sufficient conditions for some path and cycle related graphs to be edge odd graceful such as: Friendship graphs, Wheel graph, Helm graph, Web graph, Double wheel graph, Gear graph, Fan graph, Double fan graph and Polar grid graph.